RETRACTED: Differential temporal expression of S100β in developing rat brain - Patro, Nisha; Naik, Aijaz; Patro, Ishan K. (Frontiers in Cellular Neuroscience, 2015)
Radial glial cells (RGs) originally considered to provide scaffold to the radially migrating neurons constitute a heterogeneous population of the regionally variable precursor cells that generate both neurons as well as glia depending upon the location and the timing of development. Hence specific immunohistochemical markers are required to specify their spatiotemporal location and fate in the neurogenic and gliogenic zones. We hypothesize S100β as a potential and unified marker for both primary and secondary progenitors. To achieve this, cryocut sections from rat brains of varied embryonic and postnatal ages were immunolabeled with a combination of antibodies, i.e., S100β+Nestin, Nestin+GFAP and S100β +GFAP. A large population of the primary and secondary progenitors, lining the VZ and SVZ, simultaneously co-expressed S100β and nestin establishing their progenitor nature. A downregulation of both S100β and nestin noticed by the end of the 1st postnatal week marks their differentiation towards neuronal or glial lineage. In view of the absence of co-expression of GFAP either with S100β or nestin, the suitability of accepting GFAP as an early marker of RG’s was eliminated. Thus the dynamic expression of S100β in both the neural stem cells (NSCs) and RGs during embryonic and early neonatal life is associated with its proliferative potential and migration of undifferentiated neuroblasts and astrocytes. Once they lose their potential for proliferation, the S100β expression is repressed with its reemergence in mature astrocytes. This study provides the first clear evidence of S100β expression throughout the period of neurogenesis and early gliogenesis, suggesting its suitability as a radial progenitor cell marker.